Experiences in Different Activities: Temporal Dynamics and Construct Validity - Klein K.G; Leontyev D.A; Kostenko V.Yu; Osin E.N; Taranenko O.A; Kosheleva N.V (Moscow State University of Psychology and Education, 2019)
This study aims to clarify the methodological status of the category "activity experience". A sample of the study consists of first-year students of a Moscow university. Study 1 (N = 104) attended by respondent aged 17 to 28 years (M = 18.30; SD = 1.40), 82% are female, and in study 2 (N = 93), aged 17 to 28 20 years old (M = 18.02; SD = 0.61), 55% are female. Study 2 includes three measurements of activity-related experiences with an interval of 10-15 days. We use the Activity-Related Experience Assessment (AREA), the Universal Perceived Locus of Causality Scale (UPLOC), the Responsibility Scale, and a brief version of the Psychological Health Continuum. The results of the study demonstrate that the activity-related experiences are neither personality traits, that are inherent in the individual regardless of situations, nor emotional states that change over time. Evidence of reliability, construct validity and criterion validity of the Activity-Related Experiences Assessment Scale is given. The measure of academic success is better predicted not by those experiences that are manifested during study activities, but those that arise along on the way to university. There is a slight effect of the influence of time on the measure of effort.